EFFICACY OF ANGIOTENSIN RECEPTOR NEPRILYSIN INHIBITOR IN THE TREATMENT OF CHRONIC HEART FAILURE POST-COVID-19: A LONGITUDINAL STUDY - Nasirova G. A. (Scholars Digest Publishing, 2024)
Chronic heart failure (CHF) is a common sequela following COVID-19 infection, posing significant challenges in management and prognosis. Angiotensin receptor inhibitor neprilysin (ARNi) has emerged as a promising therapeutic option for CHF, but its efficacy specifically in post-COVID-19 CHF remains underexplored. Methods: We conducted a retrospective study utilizing data from 112 CHF patients with a history of COVID-19 infection. The mean age of the cohort was 62.4 ± 12.6 years, with males comprising 48% of the sample. Patients were followed up for a mean duration of 2.2 ± 1.4 years. Kaplan-Meier analysis and Cox proportional hazards model were employed to assess the efficacy of ARNi in terms of survival and clinical outcomes. Kaplan-Meier analysis revealed a significant improvement in survival rates among CHF patients treated with ARNi following COVID-19 infection compared to those receiving standard therapy (log-rank P < 0.05). The Cox proportional hazards model further confirmed the beneficial effect of ARNi, demonstrating a lower risk of mortality and CHF-related complications in the ARNi-treated group (P < 0.05). Our study provides evidence supporting the efficacy of angiotensin receptor inhibitor neprilysin for the treatment of chronic heart failure following COVID-19 infection. ARNi therapy was associated with improved survival and reduced risk of adverse clinical outcomes in this patient population.
Keywords: Angiotensin receptor inhibitor neprilysin, Chronic heart failure, COVID-19, Clinical outcomes.